2017
DOI: 10.1039/c7ra05217k
|View full text |Cite
|
Sign up to set email alerts
|

Phase tuned synthesis of titanium dioxide nanoparticles for room temperature enhanced ammonia detection

Abstract: Ionic liquid induced phase tuned TiO2 nanoparticles for ammonia gas sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
0
11
2
Order By: Relevance
“…The Psf polymer is amorphous in nature and so the neat Psf membrane shows only one broad peak at 2θ = 17.68° . The XRD patterns of the TiO 2 samples are presented elsewhere . It was observed that characteristic peaks of TiO 2 were at 27.35°, 38.12°, and 49.35°.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The Psf polymer is amorphous in nature and so the neat Psf membrane shows only one broad peak at 2θ = 17.68° . The XRD patterns of the TiO 2 samples are presented elsewhere . It was observed that characteristic peaks of TiO 2 were at 27.35°, 38.12°, and 49.35°.…”
Section: Resultsmentioning
confidence: 98%
“…Synthesized TiO 2 NPs were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and UV–visible spectroscopy. The results are reported elsewhere …”
Section: Materials and Methodsmentioning
confidence: 89%
See 3 more Smart Citations